The typology of iron nails discovered from the tomb of the martyr of Tsitsernavank - Simonyan, Hakob; Atoyants, Elena (ARAMAZD: Armenian Journal of Near Eastern Studies, 2025)
During the 1999 archaeological excavations, conducted with the aim of preparation for the restoration of a semi-ruined church, a rock-cut tomb from the Antiquity period was discovered in front of the south-western entrance to Tsitsernavank. The skeleton found here bore signs of torture. It was found in the particularly honorable place for the Armenian church – directly in front of the entrance. The traces of torment exhibited on the bones of the skeleton, as well as the discovery of unique artifacts here provide grounds to suggest that the remains of highly revered deceased person, possibly a Christian martyr, were buried here. Many rare and important artifacts were found in the tomb: a radiant-shaped cross, terracotta statuette of a woman in long garment holding a lamb in her arms (possibly representing a personification of the Virgin Mary holding an allegorical depiction of the infant Jesus), as well as iron nails that studded the skull. From the effects of rusty nails, the skull acquired the reddish hue. The burial itself, as well as the discovered artifacts, provide valuable information about ancient burial rites and the technology of iron nails’ manufacture. The nails found in close proximity to the skull contain traces of organic matter, indicating that they were used to conjoin wooden and leather components of an unknown structure.